Podnikové obligace - rozvíjející se finanční zdroj - Tetřevová, Liběna (Univerzita Pardubice, 1998)
This article deals with the corporate bonds as a developing source of funds. The corporate bonds are long-term debt securities issued by entrepreneurial subjects. These securities obligation of issuers to make payments of interest and principal on specific dates to the holder of the bond. The item also contains reasons for low usage of the corporate bonds as a source pf funds in the Czech Republic , defines main terms which are connected with this topic, mentions advantages and disadvantages of corporate bonds and informs about the situation on the bond market in the Czech Republic.
Keywords: obligace; finanční zdroje; Česká Republika